(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
The age of a person is an important characteristic that contributes to a person’s overall identity. With the growing age of a person, the incidence of tooth wear increases. It is irreversible and cumulative. Attrition means the loss of tooth substance as a result of tooth-to tooth contact. Grading tooth attrition can help as an additional tool in age estimation. We conducted this study to gauge the prevalence of dental attrition and its grading in young adults age groups in both genders. The present cross-sectional observational study was done in Srikakulam on 120 young adults, 60 male and 60 female, aged 18 to 25 years. We have modified Smith and Knight’s system and used it for our present study. Attrition of only the incisal and occlusal surfaces of teeth was studied. The data was analyzed using Fisher’s exact test. Results showed that in the studied teeth of incisors and first molars, the frequency of attrition teeth in males is 14% and in females is 18%. The lower incisors showed a greater incidence of attrition. A statistically significant correlation between age groups and attrition grade was seen in the lower incisors and lower molars of males and the upper first molars of females. So it was concluded that teeth attrition can be used as an additional tool in age estimation in young adults as well, but it can only give a wider age range.